Protocol for a realist review of General Practitioners' Role in Advancing Practice in Care Homes (GRAPE study). Issue 6 (15th June 2020) - Gordon, Adam L; Devi, Reena; Williams, Christopher; Goodman, Claire; Sartain, Kathleen; Chadborn, Neil H
Abstract : Introduction: Older people who live in care homes have a high level of need with complex health conditions. In addition to providing medical care to residents, general practitioners (GPs) play a role as gatekeeper for access to services, as well as leadership within healthcare provision. This review will describe how GPs were involved in initiatives to change arrangements of healthcare services in order to improve quality and experience of care. Methods and analysis: Following RAMESES quality and publication guidelines standards, we will proceed with realist review to develop theories of how GPs work with care home staff to bring about improvements. We identify when improvement in outcomes does not occur and why this may be the case. The first stage will include interviews with GPs to ask their views on improvement in care homes. These interviews will enable development of initial theories and give direction for the literature searches. In the second stage, we will use iterative literature searches to add depth and context to the early theories; databases will include Medline, Embase, CINAHL, PsycINFO and ASSIA. In stage 3, evidence that is judged as rigorous and relevant will be used to test the initial theories, and through the process, refine the theory statements. In the final stage, we will synthesise findings and provide recommendations for practice and policy-making. During the review, we will invite a context expert group to reflect on our findings. This group will have expertise in current trends in primary care and the care home sector both in UK and internationally. Ethics and dissemination: The study was approved by University of Nottingham Faculty of Medicine and Health Sciences Research Ethics Committee: 354-1907. Findings will be shared through stakeholder networks, published in National Institute for Health Research journal and submitted for peer-reviewed journal publication.